Latihan Fisik terhadap Kadar Glukosa Darah dan Kualitas Hidup Penderita Diabetes Melitus Tipe 2 - Titanik, Geladis; Wahyudi, Andri Setiya; Pratiwi, Ika Nur (Journal of Telenursing (JOTING), 2024)
This study aims to evaluate the effect of physical exercise on blood glucose levels and quality of life in people with Type 2 Diabetes Mellitus. Methods This research uses a systematic review method referring to PRISMA guidelines. Research shows that physical exercise, especially a combination of aerobic and resistance, effectively improves quality of life and glycemic control in type 2 diabetes patients. High-intensity exercise can improve cardiorespiratory fitness. The combination of vitamin D supplementation and exercise training has a synergistic effect in enhancing insulin resistance. Concomitant aerobic and resistance exercise is recommended for managing type 2 diabetes, with HIIT being an effective intensity option. In conclusion, physical exercise, especially a combination of aerobic and resistance, effectively improves the quality of life and glycemic control in T2DM individuals. Keywords: Physical Activity, Type 2 Diabetes Mellitus, Glucose Levels